Biomimetic Pulse Power Supply Design and Application Research Based on Electric Ray Discharge Mechanism - Li, Changhua; Wu, Shuai; Zhang, Yikai; He, Xiao; Chai, Wenping; Cai, Chunwei (IEEE Conference on Industrial Electronics and Applications (Online), 2025)
This study is grounded in the theory of the bioelectric discharge mechanism of electric rays. Through experimental testing, the discharge waveform characteristics of the electric ray's electric organ discharge (EOD) were collected, and the key electrical parameters of the discharge pulses were precisely extracted and quantitatively analyzed. Based on the physiological structure and discharge characteristics of the electric ray's electric organ, a biologically equivalent discharge model was constructed, providing a theoretical foundation for the design of a biomimetic pulse power supply. In terms of circuit design, a fully solid-state biomimetic pulse power supply prototype was designed and implemented using a switched-capacitor Marx generator topology. This power supply employs a six-stage Marx boost circuit, and by optimizing the switching timing and capacitor parameter configuration, it successfully achieved an adjustable amplitude range of 0-64.7 V, a frequency of 100Hz, and a pulse width of 2.5ms, mimicking the bioelectric discharge pulse waveform of the electric ray. To validate the design, a combination of simulation and experimental methods was used, confirming that the pulse generator can faithfully reproduce the discharge characteristics of the electric ray's electric organ. To further assess its biological effects, a controlled experiment was designed, demonstrating that the biomimetic pulse has significant advantages over traditional DC output in stimulating muscle contraction, with a lower threshold and higher efficiency in inducing muscle contraction.